Consumption in the formation of the new citizenship: from the public city to the Merchandise city - Alzate Hoyos, Cesar Andres [UNESP] (Univ Valle, 2018)
the intent of this text is to analyze the concept of citizenship analytically from two elements that are presented as two sides of the sa me coin, the public and the private, having these developments that seem increasingly to resize the right to city, and even the formation of citizenship itself, we are talking about the ways in which capital is energized by consumption, transforming a city-public into a city-merchandise. We ask ourselves in the course of this text, what derivations would a citizenship centralized in capital have, within a dear mercantile function of the city above the social function and the centrality that the public exercised over it?
Keywords: city-public; city-merchandise; property; citizenship; consumption